(untitled) (Journal of Economic Research & Business Administration, 2021)
The labor market is constantly changing, atypical work is gaining significant relevance, especially in the current time of restrictions associated with the coronavirus crisis. In Kazakhstan, the promotion of a teleworking law has made flexibility in work an interesting topic and has become an increasingly important requirement in hiring and a motivating factor for employees. In this context, this article aims to explore the relationship between employee development and flexibility in working time and workspace as important characteristics of sustainable management of human capital, job satisfaction and employee productivity. In addition, the article is aimed at studying the impact on the performance of employees of various types of flexibility – contractual, functional, working time and workspace flexibility. To emphasize the relevance of employee development and employee flexibility as important aspects of sustainable human capital management. To make this possible, a “Composite Employee Flexibility Score” was developed, which considers different types of flexibility, based on employee feedback collected through a nationally representative survey using multiple match analysis. In addition, the effect of individual flexibility and employee flexibility on overall job satisfaction was quantified using binary logistic regression models. The study reveals the concept of “work flexibility”, special attention is paid to the impact of new types of workspaces (flexible office, coworking, shared home office, partial home office) on labor productivity, job satisfaction, organizational efficiency, professional growth and development, social and professional relationships, personal professional activities, as well as the general level of work motivation. Key words: flexible management of human capital, methodology of agile HC management, project management of HC, flexibility of work, job satisfaction.